MONITORING OF INTRAMYOCARDIAL ELECTROGRAMS AND THEIR DIAGNOSTIC POTENTIAL - Hutten, H. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Purpose of work: Assessment of the potential of intramyocardial electrograms (IMEGs) for longterm cardiac telemonitoring that is not possible by surface ECG due to the poor reproducibility of these signals. Materials and methods: With the availability of cardiac pacemakers with broad-bandwidth telemetry (0,3-200 Hz) and fractally coated electrodes the monitoring of IMEGs both from the spontaneously beating and the paced heart became possible. These signals have first been utilized to monitor rejection in transplanted hearts. Protocols for standardized clinical examinations have been set up that allow to eliminate errors (e.g. time of day, changes in posture, and stimulation parameters). Tailored software has been developed for signal processing based on event classification, averaging, and parameter extraction. Individual features like anatomy of the heart and respective position of the electrode require that each patient is considered for its own reference. Results: IMEGs can be acquired with excellent longterm reproducibility of signal morphology. In most cases the transitory effects during the post-implant period can appropriately be considered. Regarding reproducibility the IMEGs are superior to surface electrograms. Careful signal processing of the structured morphology of IMEGs supplies information of clinical relevance that can not be obtained from surface electrograms. Ventricular evoked responses (VERs) can be obtained with the same electrode that is used for stimulation. VERs in transplanted hearts do indicate not only acute rejection and infection episodes, but have a high prognostic potential for recipient monitoring. Furthermore, IMEGs monitor information on the hemodynamic situation of the heart, e.g. end-diastolic filling volume, and they can be utilized for AV-setting in patients with cardiomyopathies. Conclusion: Surface electrograms are well established for cardiac routine diagnosis and longterm monitoring, e.g. Holter monitoring. However, thanks to progress in pacemaker technology IMEGs offer another challenging potential for cardiac monitoring including therapy management and risk surveillance that is not accessible with surface electrograms. Computerized evaluation of IMEGs is possible, however requires tailored software that is made available by specialized centers.